LEADER-MEMBER EXCHANGE, COMMUNICATION SATISFACTION, JOB SATISFACTION, EMPLOYEE ENGAGEMENT DAN EMPLOYEE PERFORMANCE - Arfian Oktaviandi Rizky; Abdul Haeba Ramli; Siti Mariam (POLITEKNIK LP3I JAKARTA, 2023)
After the pandemic in Indonesia and even the world ended, many industrial companies began to revive by focusing on improving the performance of their companies. Then the company will need high-performing employees in order to help the company return to its previous performance even higher. The purpose of this research is to determine the effect of Communication Satisfaction, Leader-Member Exchange, Job Satisfaction and Employee Engagement on Employee Performance in Industrial Companies. This data collection was carried out by distributing questionnaires to 116 respondents who were employees in industrial companies in the June 2023 period. In this research the method used for data processing and analysis was Structural Equation Model Partial Least Square (SEM-PLS). The results showed that Communication Satisfaction has a positive effect on Employee Engagement, Communication Satisfaction has a positive effect on Job Satisfaction, Communication Satisfaction has a positive effect on Employee Performance, Leader-Member Exchange (LMX) has no positive effect on Employee Engagement, Employee Engagement has a positive effect on Employee Performance, Job Satisfaction has a positive effect on Employee Engagement, Job Satisfaction has no positive effect on Employee Performance. The industry is expected to increase Job Satisfaction by increasing employee safety while working, for example by adding security services and working hours that are not exceeding the provisions, but it can also be increased through the provision of adequate compensation.Keywords: Communication Satisfaction, Leader-Member Exchange, Job Satisfaction, Employee Engagement, Employee performance